Joint trajectory design and resource allocation for UAV-assisted mobile edge computing in power convergence network - Junbin Cui; Yong Wei; Jianbo Wang; Li Shang; Peng Lin (EURASIP Journal on Wireless Communications and Networking)
Abstract In the power convergence network, a large number of intelligent power terminals (IPTs) are deployed, such as a variety of information collection terminals. Meanwhile, the unmanned aerial vehicles (UAVs) offer dependable services for IPTs in environments with minimal or no infrastructure and then combine with the mobile edge computing to realize low-latency task services. In this article, we consider a problem of computation offloading and UAV trajectory design to minimize the task offloading delay. Because the primal problem is non-convex, we first decompose it into two subproblems, i.e., joint computation offloading and resource allocation subproblem, and UAV trajectory design subproblem. For the first subproblem, we first reformulate it as a non-convex problem. And then, recognizing the problem’s high complexity, we choose to decompose it in a distributed form. Following this, leveraging the alternating direction method of multipliers, we introduce the joint computation offloading and resource allocation algorithm. For the second subproblem, we utilize the successive convex approximation method to solve this non-convex problem. Utilizing the solutions obtained from these two subproblems, we have introduced the joint computation offloading and UAV trajectory design (JCOUTD) algorithm to tackle the primal problem. The simulation results reveal that in comparison with other benchmark methods, the proposed JCOUTD algorithm displays enhanced performance in reducing total task offloading delay.